The Opioid-Sparing Effect of Acupuncture After Abdominal Surgery: A Systematic Review and Meta-Analysis Protocol - Joo, Chanwoo; Kim, Kun Hyung; Jang, Bo-Hyoung; Huang, Ching-Wen; Kang, Jung Won; Lee, Jae-Dong; Lee, Suji; Lee, Seunghoon (Journal of pain research, 2023)
Routine overprescribing of postoperative opioid analgesics may induce side effects and correlate with chronic opioid use following surgery. This review aims to evaluate the effectiveness and safety of acupuncture for opioid-sparing effects in patients who underwent abdominal surgery. Eleven databases in different languages, including English (Ovid MEDLINE, CENTRAL, EMBASE, CINAHL), Chinese, Korean, and Japanese, will be searched. Randomized controlled trials using acupuncture for postoperative pain control in adult patients undergoing abdominal surgery will be screened. All randomized controlled trials comparing acupuncture with no treatment, sham acupuncture, and conventional treatments will be included. The Cochrane risk of bias tool will be used to assess the risk of bias. The primary outcome will consist of a cumulative opioid consumption. Additionally, the number of cumulative opioid analgesic demands/requests, the time to initial opioid analgesic usage, postoperative pain, opioid-related side effects, and adverse events of acupuncture will be assessed. The mean differences or risk ratios with a 95% confidence interval will be calculated to estimate the pooled effect of acupuncture when it is possible to conduct a meta-analysis. This study could confirm the effect of opioid-sparing on acupuncture after abdominal surgery. This study would evaluate the evidence on the effectiveness of acupuncture after abdominal surgery with a focus on opioid intake. It provides evidence to support decision-making on applying acupuncture for postoperative management. CRD42022311155.